Poly(L-histidine)-tagged 5-aminolevulinic acid prodrugs: new photosensitizing precursors of protoporphyrin IX for photodynamic colon cancer therapy - Johnson RP (Dove Medical Press, 2012)
Renjith P Johnson,1* Chung-Wook Chung,2* Young-Il Jeong,2 Dae Hwan Kang,2 Hongsuk Suh,3 Il Kim,11WCU Centre for Synthetic Polymer Bioconjugate Hybrid Materials, Department of Polymer Science and Engineering, Pusan National University, Pusan, 2National Research and Development Center for Hepatobiliary Cancer, Pusan National University, Yangsan Hospital, Yangsan, Gyeongnam, 3Department of Chemistry and Chemistry Institute for Functional Materials, Pusan National University, Pusan, Korea*These authors contributed equally to this workBackground: 5-Aminolevulinic acid (ALA) and its derivatives have been widely used in photodynamic therapy. The main drawback associated with ALA-based photodynamic therapy (ALA-PDT) and ALA fluorescence diagnosis results from the hydrophilic nature of ALA and lack of selectivity for tumor versus nontumor cells. The application of certain triggers, such as pH, into conventional sensitizers for controllable 1O2 release is a promising strategy for tumor-targeted treatment.Methods: A series of pH-sensitive ALA-poly(L-histidine) [p(L-His)n] prodrugs were synthesized via ring opening polymerization of 1-benzyl-N-carboxy-L-histidine anhydride initiated by the amine hydrochloride group of ALA itself. As an alternative to ALA for PDT, the synthesized prodrugs were used to treat a cultured human colon cancer HCT116 cell line under different pH conditions. The effect of ALA-p(L-His)n derivatives was evaluated by monitoring the fluorescence intensity of protoporphyrin IX, and measuring the cell survival rate after suitable light irradiation.Results: The cytotoxicity and dark toxicity of ALA and synthesized ALA-p(L-His) derivatives in HEK293T and HCT116 cells in the absence of light at pH 7.4 and 6.8 shows that the cell viability was relatively higher than 100%. ALA-p(L-His)n showed high phototoxicity and selectivity in different pH conditions compared with ALA alone. Because the length of the histidine chain increases in the ALA-p(L-His)n prodrugs, the PDT effect was found to be more powerful. In particular, high phototoxicity was observed when the cells were treated with ALA-p(L-His)15, compared with treatment using ALA alone.Conclusion: The newly synthesized ALA-p(L-His)n derivatives are an effective alternative to ALA for enhancing protoporphyrin IX production and the selectivity of the phototoxic effect in tumor cells.Keywords: 5-aminolevulinic acid, photodynamic therapy, poly(L-histidine), bioconjugate, cancer cells